548. Baseline characteristics associated with clinical improvement and mortality in hospitalized patients with moderate COVID-19. (31st December 2020) - Castagna, Antonella; Hui, David Shu Cheong; Mullane, Kathleen M; Mullane, Kathleen M; Jain, Mamta; Galli, Massimo; Chang, Shan-Chwen; Hyland, Robert H; SenGupta, Devi; Cao, Huyen; Huang, Hailin; Chokkalingam, Anand; et al.
Abstract: Background: Remdesivir (RDV) has been shown to shorten recovery time and was well tolerated in patients with severe COVID-19. Here we report baseline characteristics associated with clinical improvement at day (d) 14. Methods: We enrolled hospitalized patients with confirmed SARS-CoV-2 infection, oxygen saturation >94% on room air, and radiological evidence of pneumonia. Patients were randomized 1:1:1 to receive 5d or 10d of intravenous RDV once daily plus standard of care (SoC), or SoC only. For this analysis, patients were followed through discharge, d14, or death. Baseline demographic and disease characteristics associated with clinical improvement in oxygen support (≥2-point improvement on a 7-category ordinal scale ranging from discharge to death) were evaluated using multivariable logistic regression methods. Results: 584 patients were randomized and treated (5/10d RDV, n=384; SoC: n=200). 159 (27%) were ≥65y, 227 (39%) female, 328 (61%) white, 102 (19%) Asian, and 99 (19%) Black. 252 participants (43%) were enrolled in Europe, 260 (45%) North America (NA), and 72 (12%) in Asia. Most patients (483 [83%]) were not on supplemental oxygen but required medical care at baseline. In a multivariable model, 5/10d RDV was significantly positively associated with clinical improvement (adjusted odds ratio [OR] 1.69, 95% CI: 1.08, 2.65; p=0.0226). Significant covariables positively associated with clinical improvement included age < 65y (p< 0.0001) and region of treatment (Europe and NA vs Asia, p< 0.0001 each; Table); other examined factors were not significantly associated with clinical improvement, including gender, race, ethnicity, baseline oxygen support, duration of symptoms and hospitalization, obesity, and baseline transaminase levels. Table 1. Conclusion: In moderate COVID-19 patients, after adjusting for treatment arm, age < 65y and region (NA vs Asia; Europe vs Asia) were associated with higher rates of clinical improvement. These observations recapitulate younger age as positive prognostic factor, and highlight the differences in the impact of the pandemic globally. Disclosures: Antonella Castagna, MD, Gilead Sciences Inc. (Scientific Research Study Investigator) David Shu Cheong Hui, MD, Gilead Sciences Inc. (Scientific Research Study Investigator) Kathleen M. Mullane, DO, PharmD, Gilead Sciences Inc. (Grant/Research Support, Scientific Research Study Investigator) Mamta Jain, MD, Gilead Sciences Inc. (Scientific Research Study Investigator, Research Grant or Support)GlaxoSmithKline (Advisor or Review Panel member)Janssen (Research Grant or Support)Merck (Research Grant or Support) Massimo Galli, MD, Gilead Sciences Inc. (Grant/Research Support, Scientific Research Study Investigator, Advisor or Review Panel member, Other Financial or Material Support, Personal fees) Shan-Chwen Chang, MD, PhD, Gilead Sciences Inc. (Scientific Research Study Investigator) Robert H. Hyland, MD, Gilead Sciences Inc. (Employee, Shareholder) Devi SenGupta, MD, Gilead Sciences Inc. (Employee, Shareholder) Huyen Cao, MD, Gilead Sciences Inc. (Employee, Shareholder) Hailin Huang, PhD, Gilead Sciences Inc. (Employee, Shareholder) Anand Chokkalingam, PhD, Gilead Sciences (Employee) Anu Osinusi, MD, Gilead Sciences (Employee) Diana M. Brainard, MD, Gilead Sciences (Employee) Christoph Lübbert, MD, Gilead Sciences Inc. (Scientific Research Study Investigator) David Chien Boon Lye, MD, Gilead Sciences Inc. (Scientific Research Study Investigator) David Chien Boon Lye, MD, NO DISCLOSURE DATA Judith A. Aberg, MD, Theratechnology (Consultant) Enrique Navas Elorza, MD, Gilead Sciences Inc. (Scientific Research Study Investigator) Karen T. Tashima, MD, Bristol-Myers Squibb (Research Grant or Support)Gilead Sciences Inc. (Grant/Research Support, Scientific Research Study Investigator)GlaxoSmithKline (Research Grant or Support)Merck (Research Grant or Support)Tibotec (Research Grant or Support)Viiv Healthcare (Research Grant or Support) Mark McPhail, MD, Gilead Sciences Inc. (Scientific Research Study Investigator)